Qualitative research methods in human geography - edited by Iain Hay; Hay, Iain, 1960 (Don Mills, Ontario : Oxford University Press, 2016)
"Qualitative Research Methods in Human Geography is a comprehensive, practical guide to understanding and conducting qualitative research in human geography. Using a unique "how-to" approach to focus on the practical application of research in human geography by providing real-world examples of research methods at work in case studies, this fourth edition teaches students how to plan, execute, interpret, and effectively communicate qualitative research. With the inclusion of new Canadian and North American examples throughout, in addition to international and Asia-Pacific examples, the text achieves its goal of providing an in-depth overview of qualitative research methods relevant to human geography that is both readable and accessible for students. Now in its fourth edition, Qualitative Research Methods in Human Geography returns with improved readability for undergraduate students, end-of-chapter review exercises, and an appendix of example field notes, making the text much more accessible, current, andrelevant to today's human geography students. Three new chapters have also been added on the topics of feminist and indigenous approaches, visual methods, and new media."--
Includes bibliographical references (pages 459-494) and index.
Keywords: Human geography -- Methodology -- Textbooks; Qualitative research -- Textbooks; Human geography -- Methodology; Qualitative research; Textbooks